Reading Vincent van Gogh: a Thematic Guide to the Letters - Patrick Grant (Athabasca University Press, 2016)
Soon after his death, Vincent van Gogh$1 (Bs reputation grew and developed through the remarkably symbiotic relationship evident between his paintings and letters. However, the sheer bulk and complexity of Van Gogh$1 (Bs complete surviving correspondence presents a formidable challenge to those who wish to read and analyze the whole text as a literary work. Reading Vincent van Gogh is at once an interpretive guide to Van Gogh$1 (Bs letters and a distillation of the key themes that reoccur throughout his collected letters$1 (Bforemost among them the motifs of suffering, love, imagination, and the ineffable. In this indispensable, synoptic view of the letters, Patrick Grant makes the main lines of Vincent van Gogh$1 (Bs thinking accessible and displays the arresting vividness of the well-known artist$1 (Bs writing.s
English
Keywords: painter; art history; aphorisms; writer; imagination; spirituality